Librarian Competency Development in Supporting Education Management and Collaborative Learning in Schools - Zikry Saba, Zikry Indra (JME Jurnal Management Education, 2025)
This study examines the strategic role of school librarians in supporting educational management and collaborative learning. In this context, librarians serve as learning facilitators, not only managing reading materials but also assisting students and teachers in accessing information and developing essential information literacy and critical thinking skills in the digital age. The research findings indicate that competent school librarians are able to serve as a bridge between learning resources and students' learning needs. However, the development of librarians' competencies is still hindered by the limited availability of specialized training programs and inadequate infrastructure support from the school. As a result, some librarians remain stuck in traditional administrative roles and are less effective in facilitating collaborative learning. To address this issue, the study recommends implementing ongoing digital literacy training for librarians, strengthening collaboration between librarians and teachers, and enhancing infrastructure support from the school. By applying these strategies, it is hoped that librarians can play a more effective role in supporting educational management and creating a dynamic collaborative learning environment, ultimately improving the quality of education in schools.